CPW-Fed Microstrip Patch Antenna for Millimeter Wave Applications - Shaik, Khader Zelani; p, Siddaiah; k, Satya Prasad (International Journal of Integrated Engineering, 2022)
The antenna elements have been consuming more power and inoperative area with high operational frequency. Therefore, an advanced antenna element design is necessary to cross over the above faults. In this research work, the CPW-Fed microstrip patch antenna is designed using EHF range for millimeter-wave applications. CPW-fed and combinations of DGS-CPW-fed microstrip patch antennas are novel methods, these designs are enhancing many characteristics of microwave circuits, such as narrow bandwidth, cross-polarization, low gain, etc. The researchers are facing many issues in this research area, therefore Fed-CPW design has been taken as a challenging issue. Investigators are working on wideband antennas, as well as patch antennas that can be used for both single- and dual-band applications. In addition to multiband applications, DGS, CPW-Fed Slot antennas are loaded with filters, these enhancements are providing waveguides and amplification tuning.The proposed research deals with a CPW-Fed Microstrip Patch satellite antenna, which is specially modeled to operate at various high-frequency values as well as Extremely High Frequency (EHF) range. A T-Shaped Microstrip patch antenna, which is dimensioned at 11.4x2.5x1.6 mm3 has been placed on Rogers R04003 substrate. The proposed antenna has CPW-Fed with ground dimensions which are considered as 5.9mm*8mm & feed dimensions as 3.8mm*9mm. Due to CPW-feed, the proposed antenna has achieved huge bandwidth i.e 13GHz. Hence the proposed antenna design is compact and suitable at higher frequencies. Simulation results approve that it is a good antenna model. The performance measures like return loss, gain, and VSWR has been improved compared to earlier models. Moreover, this CPW-fed microstrip patch antenna approach is most useful for 5G applications and simulation results are outperforms with designed frameworks.The proposed antenna resonates from 24GHz to 37.6GHz, with good impedance matching at |S11|